2007
DOI: 10.1128/jb.00089-07
|View full text |Cite
|
Sign up to set email alerts
|

Complete Nucleotide Sequence of the 113-Kilobase Linear Catabolic Plasmid pAL1 of Arthrobacter nitroguajacolicus Rü61a and Transcriptional Analysis of Genes Involved in Quinaldine Degradation

Abstract: The nucleotide sequence of the linear catabolic plasmid pAL1 from the 2-methylquinoline (quinaldine)-degrading strain Arthrobacter nitroguajacolicus Rü61a comprises 112,992 bp. A total of 103 open reading frames (ORFs) were identified on pAL1, 49 of which had no annotatable function. The ORFs were assigned to the following functional groups: (i) catabolism of quinaldine and anthranilate, (ii) conjugation, and (iii) plasmid maintenance and DNA replication and repair. The genes for conversion of quinaldine to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
26
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 69 publications
1
26
0
Order By: Relevance
“…The adjacent gene pAL1.101 codes for a putative telomere-associated protein, which, however, is much larger than the Tap proteins of Streptomyces linear replicons. We hypothesized that the pAL1.101 protein might play a different, or more versatile, role in the replication of linear DNA than the Tap proteins (36). In this study, we show that the protein interacts with TP pAL1 in vivo.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…The adjacent gene pAL1.101 codes for a putative telomere-associated protein, which, however, is much larger than the Tap proteins of Streptomyces linear replicons. We hypothesized that the pAL1.101 protein might play a different, or more versatile, role in the replication of linear DNA than the Tap proteins (36). In this study, we show that the protein interacts with TP pAL1 in vivo.…”
mentioning
confidence: 59%
“…The 113-kb conjugative plasmid pAL1, which confers on Arthrobacter nitroguajacolicus Rü61a the ability to utilize the N-heteroaromatic compound 2-methylquinoline, is so far the only described linear plasmid within this genus. The termini of pAL1 show the inverted-repeat sequence 5Ј-CCTGC…GCAGG-3Ј, and its 5Ј ends are capped with proteins (34,36). The terminal protein TP pAL1 is encoded by the pAL1.102 locus, which is located close to the "right" terminus of pAL1 (30).…”
mentioning
confidence: 99%
“…Previous sequence analysis of the promoter regions of meqC (formerly, qox), meqD (formerly, moq), and ORF19 had suggested that meqCp and meqDp likely are 70 -dependent promoters, whereas ORF19p possibly is recognized by 38 -polymerase (13). As a first step to characterize the meqR2 promoter, the transcriptional start of meqR2 was mapped by 5=-RACE analysis to the position 250 nucleotides upstream of the translation initiation codon.…”
Section: Meqr2 Repressor Involved In Quinaldine Catabolismmentioning
confidence: 99%
“…1B), show significant similarity to those of 2-aminobenzoate CoA ligase and 2-aminobenzoyl-CoA monooxygenase/reductase of Azoarcus evansii, respectively. Transcription of the three catabolic operons on pAL1 is upregulated in cells grown on quinaldine or on aromatic compounds downstream in the degradation pathway (13); however, the molecular basis of transcriptional control has remained unresolved.…”
mentioning
confidence: 99%
See 1 more Smart Citation